Survival in primary antiphospholipid syndrome - Ames, Paul R. J.; Merashli, Mira; Ster, Irina Chis; D’Andrea, Giovanna; Iannaccone, Luigi; Marottoli, Vincenzo; Margaglione, Maurizio; Brancaccio, Vincenzo (Thrombosis and Haemostasis, 2016)
The vascular mortality of antiphospholipid syndrome (APS) ranges from 1.4 % to 5.5 %, but its predictors are poorly known. It was the study objective to evaluate the impact of baseline lupus anticoagulant assays, IgG anticardiolipin (aCL), plasma fibrinogen (FNG) and von Willebrand factor (VWF), platelets (PLT) and of genetic polymorphisms of methylenetetrahydrofolate reductase C677T, of prothrombin G20210A and of paraoxonase-1 Q192R on survival in primary APS (PAPS). Cohort study on 77 thrombotic PAPS and 33 asymptomatic carriers of aPL (PCaPL) seen from 1989 to 2015 and persistently positive for aPL as per annual review. At baseline all participants were tested twice for the ratios of kaolin clotting time (KCTr), activated partial thromboplastin time (aPTTr), dilute Russell viper venom time (DRVVTr), IgG aCL, FNG, VWF and once for PLT. All thrombotic PAPS were on warfarin with regular INR monitoring. During follow-up 11 PAPS deceased (D-PAPS) of recurrent thrombosis mostly arterial, despite adequate anticoagulation yielding an overall vascular mortality of 10 %. D-PAPS had the strongest baseline aPTTr and DRVVTr and the highest mean baseline IgG aCL, FNG, VWF and PLT. Cox proportional hazards model identified baseline DRVVTr and FNG as main predictors of mortality with adjusted hazard ratios of 5.75 (95 % confidence interval [CI]: 1.5, 22.4) and of 1.03 (95 %CI: 1.01, 1.04), respectively. In conclusion, plasma DRVVTr and FNG are strongly associated with the risk of vascular death in PAPS; while FNG lowering agents exist further research should be directed at therapeutic strategies able to dampen aPL production.
Keywords: Antiphospholipid syndrome; DRVVT; fibrinogen; mortality